ANALISIS PENGARUH NON-INTERNET DAN SOCIAL MEDIA PROMOTION TERHADAP BRAND EQUITY (Studi Pada Produk Lipstick Pixy di Kota Semarang) - Salsabella, Shella; Sukresna, I Made (Faculty of Economics and Business Diponegoro University, 2021)
ABSTRACT The competition in cosmetics industry is increasing over time. Therefore, companies are competing to make products that consumers like and make strategies to sell their products. Through this competition there is a ranking of the most favorite brands according to the Top Brand Index. The purpose of this study was to determine the effect of non-internet promotion and social media promotion on brand equity with brand experience as an intervening variable and perceived quality as a moderating variable in Pixy lipstick products in Semarang. The population in this study are Pixy lipstick consumers in Semarang. The number of sample used was 175 people who were selected using purposive sampling through a questionnaire. The data obtained is then analyzed using the AMOS program. The results of the study showed that non internet promotion and social media promotion variables had positive effect on brand experience, and the results of the study also showed that perceived quality variable can moderate the effect of brand experience on brand equity.